2001
DOI: 10.1159/000051684
|View full text |Cite
|
Sign up to set email alerts
|

Cowden Syndrome – Diagnostic Skin Signs

Abstract: Cowden syndrome is a rare autosomal dominant familial cancer syndrome with a high risk of breast cancer. The most important clinical features include carcinomas of the breast and thyroid, and hamartomatous polyps of the gastrointestinal tract. There are characteristic mucocutaneous features which allow early recognition of the disease and are generally present before internal malignancies develop. We report on a woman in whom the diagnosis of Cowden syndrome was first made after she had been treated for both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 23 publications
0
47
1
4
Order By: Relevance
“…The skin of these mice shows focally increased epidermal thickness due to hyperkeratosis (Di Cristofano et al 1998), a feature commonly observed with CD patients. The association of squamous cell carcinomas with CD has also been reported (Camisa et al 1984;Hildenbrand et al 2001), but these lesions were not observed in Pten +/− animals. On the other hand, 100% of mice with complete Pten deficiency, and a proportion with Pten heterozygosity, in their keratinocytes spontaneously develop papillomas and squamous cell carcinomas (Suzuki et al 2003), indicating that Pten is an important suppressor of skin tumorigenesis.…”
mentioning
confidence: 53%
“…The skin of these mice shows focally increased epidermal thickness due to hyperkeratosis (Di Cristofano et al 1998), a feature commonly observed with CD patients. The association of squamous cell carcinomas with CD has also been reported (Camisa et al 1984;Hildenbrand et al 2001), but these lesions were not observed in Pten +/− animals. On the other hand, 100% of mice with complete Pten deficiency, and a proportion with Pten heterozygosity, in their keratinocytes spontaneously develop papillomas and squamous cell carcinomas (Suzuki et al 2003), indicating that Pten is an important suppressor of skin tumorigenesis.…”
mentioning
confidence: 53%
“…Among the characteristic symptoms of Cowden disease are trichilemmomas in the face skin papules, papillomatosis in the mucosal and cutaneous tissues, and hyperkeratosis in the acral region of the skin (Hildenbrand et al, 2001). The association of cutaneous squamous cell carcinomas with Cowden disease has also been reported (Camisa et al, 1984;Nuss et al, 1978).…”
Section: Role Of Pten In Keratinocytesmentioning
confidence: 99%
“…4 Often, the potential for internal malignancy is first suspected when the skin disease is recognized. The skin changes are protean and are described below.…”
Section: Inherited Syndromesmentioning
confidence: 99%
“…A variety of cutaneous and mucosal manifestations can occur; these are observed at any time from childhood to middle age. [4][5][6][7] Small (1-4 mm) flesh-colored papules (trichilemmomas) are found mainly on the head and neck and may assume a wartlike appearance (Fig. 1).…”
Section: Cowden Syndrome (Multiple Hamartoma Syndrome)mentioning
confidence: 99%
See 1 more Smart Citation